Tort Claim under the Ship Time Charter: The Perspective of Indonesian Law - Kartika Paramita (Universitas Lampung, 2021)
During a cargo carriage by sea under the time charter scheme, there can be a situation where the Ship-owner of the vessel does not have a contractual relationship with the cargo owner. This situation could happen when the charterer becomes the contractual carrier under the bill of lading instead of the Ship-owner. In that given scenario, if cargo damage occurs, the cargo owner can submit a tort claim against the Ship-owner. Indonesia never ratifies an international convention in the field of carriage of goods by sea. Suppose the given scenario happens without the incorporation of the Charter party or the provision of any international convention into the bill of lading, a tort claim will become a choice for the cargo owner to ask the Ship-owner's liability. It is the purpose of this article to analyze how Indonesian laws will examine a tort claim and how the Ship-owner will construe his defense in the field of carriage of goods by sea. The writing finds that Indonesia Commercial Code provides a legal basis for a cargo owner's tort claim against the Ship-owner. However, it needs further discussion to set the relationship status among the Ship-owner, the time-charterer/contractual carrier, and the cargo owner under Indonesian laws and regulations.